Amine-functionalized bimetallic Co/Zn-zeolitic imidazolate frameworks as an efficient catalyst for the CO(2 )cycloaddition to epoxides under mild conditions - Nguyen, Que Thi; Do, Xuan Huy; Cho, Kie Yong; Lee, Yu-Ri; Baek, Kyung-Youl (Elsevier BV, 2022)
Amine-functionalized bimetallic zeolitic imidazolate framework-8 (Co/Zn-ZIF-A) with 3-amino-1,2,4-triazole (Atz) was synthesized by a post-synthetic modification and utilized as a heterogeneous catalyst for the synthesis of cyclic carbonates from CO2 and epoxides. Different amine contents in Co/Zn-ZIF-A materials were controlled by adjusting the ligand exchange reaction time of the of 2-mIM with Atz. Co/Zn-ZIF-A-24 h with the highest amine contents (32% of Atz) achieved an excellent result of 99% conversion of epichlorohydrin with high selectivity of > 99% after 24 h without co-catalyst and solvent under mild conditions (80 oC, 1 bar CO2). The enhanced catalytic activity is attributed to the acid-base synergistic effect by the combination of bimetallic systems consisting of Zn and Co as Lewis acid sites and the abundant Lewis bases sites of -NH2, -NH groups from Atz ligand. A kinetic study of the cycloaddition reaction over Co/Zn-ZIF-A-24 h confirmed an approximately firstorder dependence on the epichlorohydrin concentration and CO2 pressure with an activation energy of approximately 39.5 kJ mol-1. Co/Zn-ZIF-A-24 h catalyst showed good reusability with no obvious loss in catalytic activity during five recycling runs and its structural stability was also confirmed. A plausible reaction mechanism of Co/Zn-ZIF-A catalyst for CO2-epoxide cycloaddition was proposed.